ECOLOGICAL ENERGY AS A STRATEGIC DIRECTION FOR ENSURING ENERGY SECURITY - SHPATAKOVA, Oksana; ZHURAVEL, Mykola; SLOBODIAN, Nazar (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The problem of ensuring energy security remains one of the most pressing tasks for modern states. In the context of rapid growth in energy consumption and limited traditional energy resources, the development of environmental energy is acquiring strategic importance. The main challenges in this area include high initial investment, the need for infrastructure development and technological limitations. At the same time, green energy makes it possible to reduce dependence on imported energy resources, reduce the negative impact on the environment and create new jobs. It is also important to consider the social and economic aspects of green energy integration, such as public support and attracting investment. International experience shows that successful integration of renewable energy sources is possible with an integrated approach that includes government support, international cooperation and innovation. To ensure energy security, it is necessary to develop and implement strategic directions that promote the development of environmental energy and its integration into national energy systems. The article is aimed at studying the current state of environmental energy, identifying key factors and barriers, as well as developing recommendations for public policy and attracting investment in this area. The use of an integrated approach and international experience will significantly increase the level of energy security and sustainability of energy systems. Analysis of recent studies and publications shows that technological innovation plays a key role in expanding the use of renewable energy sources. For example, Jacobson M. Z. et al propose roadmaps for 139 countries to transition to 100% renewable energy, Owens B. describes technology roadmaps for solar photovoltaic energy, and Pfenninger S. et al highlight the importance of open data and software. In addition, the successful experience of countries such as Germany, China and Denmark demonstrates the importance of public-private partnerships, as well as international cooperation in the development of green energy. An analysis of the current state of environmental energy shows that the share of renewable energy sources in global electricity production is constantly increasing. The main growth drivers are falling technology costs, government support and awareness of climate change. Leading countries such as Germany, China and the USA are actively investing in the development of solar and wind energy, which helps reduce dependence on traditional energy resources and improve the environmental situation. In conclusion, green energy plays an important role in energy security, providing both economic and environmental benefits. Despite existing challenges, the development and integration of renewable energy sources is a strategic direction to help reduce dependence on traditional energy sources and ensure a sustainable energy future.
Keywords: environmental energy; energy security; renewable energy sources; sustainable development; government support; technological innovation; international cooperation; energy infrastructure; investment; climate change